The Interactions between Microfinance Institutions and Small and Medium Scale Enterprises in the Sunyani Municipality of Ghana - Awuah, Samuel Baffour; Addaney, Michael (Asian Development Policy Review, 2016)
Small and Medium Scale Enterprises play a significant role in the global economy and hence, considered as the backbone of the private sector. SMEs play a vital role in economic, social and cultural development. Studies indicate that microfinance services and products over time have positive effects on SMEs. Conversely, other scholars have highlighted that microfinance has impacted negatively on SMEs, especially, those owned or operated by women. Thus, the study sought to establish the effects of microfinance on SMEs. The study adopted a case study approach. It examined the effects of microfinance services and products provided by Multi Credit Savings and Loans Limited on the performance of SMEs in the Sunyani Municipality of Ghana and also examined the problems encountered by both in dealing with each other. In all, questionnaires were administered to 152 customers of MCSL who were owners of SMEs. The study found that the main challenges faced by SMEs include short duration of loans repayment, high interest rates and request for collateral among others. Also, the study established that the effect of microfinance institutions on SMEs was positive. Revenue, profit and assets base of SMEs increased over time when they patronised the services of microfinance institutions. The study, therefore, recommended that microfinance institutions should make their products more SME friendly, institute more business advisory services, and ensure the proper application of loans contracted from them through effective monitoring systems. SMEs on the other hand, are to diligently keep record books for self-assessment and hire competent staff to improve their management capacities.